Access and communication for deaf individuals in Australian primary care - Phoebe H. Lee (Wiley, 2021)
Abstract Background and Aims The Australian Deaf Community face barriers that impede their access to, and communication within, primary health care settings. This study aimed to identify barriers and facilitators to access and communication for deaf individuals and Auslan interpreters in Australian general practice settings. Methods Semi‐structured interviews were conducted with eight Auslan interpreters and four deaf participants recruited from interpreter organisations and social media. Transcripts of interviews were coded inductively and deductively based on a model of access to health care. Results Patient, provider and contextual factors were reported. Patient barriers included English and Auslan fluency levels within the Australian Deaf Community. GP clinics varied in the degree of accommodation to the needs of deaf people. There were barriers related to the communication methods used by health care providers and their use of interpreters. Visual aids and flexibility in terms of the GP clinics' appointment systems facilitated access. Contextual barriers included the shortage of Auslan interpreters and the complexity of the National Disability Insurance Scheme. Conclusion The main barriers identified concerned the availability of interpreters, accommodation by health providers, cultural sensitivity and the adequacy of communication methods. Research is needed to explore the limitations of the National Disability Insurance Scheme and interventions to improve GPs' skills in communicating with Deaf individuals. Patient or Public Contribution A researcher with a hearing impairment and experience in working with people with hearing impairments was consulted on study design and interview questions. Recruitment was assisted by Auslan interpreter agencies and a Deaf Community Facebook group.